2016
DOI: 10.1371/journal.pone.0145735
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology and Whole Genome Sequencing Analysis for an Outbreak of Bovine Tuberculosis in Beef Cattle and White-Tailed Deer in Northwestern Minnesota

Abstract: Bovine tuberculosis (bTB) was discovered in a Minnesota cow through routine slaughter surveillance in 2005 and the resulting epidemiological investigation led to the discovery of infection in both cattle and white-tailed deer in the state. From 2005 through 2009, a total of 12 beef cattle herds and 27 free-ranging white-tailed deer (Odocoileus virginianus) were found infected in a small geographic region of northwestern Minnesota. Genotyping of isolates determined both cattle and deer shared the same strain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 19 publications
0
46
1
1
Order By: Relevance
“…In comparison with our study, studies from the United States found that being foreign born (in particular, being of Hispanic ethnicity) and younger were independently associated with M. bovis when compared with M. tuberculosis ( 35 , 36 ). The difference in demographic characteristics of M. bovis patients in the United States and in England, Wales, and Northern Ireland may be explained by the fact that M. bovis in cattle or wildlife is not frequently reported in the United States ( 37 , 38 ) but is more common in neighboring Mexico ( 39 , 40 ). Thus, the epidemiology of human M. bovis in England, Wales, and Northern Ireland continues to be driven by the past and, to some extent, present prevalence of disease in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with our study, studies from the United States found that being foreign born (in particular, being of Hispanic ethnicity) and younger were independently associated with M. bovis when compared with M. tuberculosis ( 35 , 36 ). The difference in demographic characteristics of M. bovis patients in the United States and in England, Wales, and Northern Ireland may be explained by the fact that M. bovis in cattle or wildlife is not frequently reported in the United States ( 37 , 38 ) but is more common in neighboring Mexico ( 39 , 40 ). Thus, the epidemiology of human M. bovis in England, Wales, and Northern Ireland continues to be driven by the past and, to some extent, present prevalence of disease in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome sequencing was performed at the National Veterinary Services Laboratory of APHIS-USDA (NVSL-APHIS-USDA) in Ames, Iowa, USA, according to their own protocols [25]. Isolates were sequenced using a MiSeq (Illumina, San Diego, CA) and the Nextera XT library preparation kit (Illumina, San Diego, CA).…”
Section: Whole Genome Sequencing and Phylogenetic Analysismentioning
confidence: 99%
“…To date, the only apparently successful eradication of M. bovis in wild cervids has been in Minnesota, which had by far the smallest and most recent of the 3 outbreaks. Greater than 10,000 Minnesota deer were tested, with the deer population in the affected area reduced by an estimated 55% in 4 years at an estimated cost of US$86 million in federal and state expenditures (Carstensen and DonCarlos , Glaser et al ). The future expenditure needed to achieve M. bovis eradication in Michigan has been estimated to be ≥US$1.5 million annually over the next 30 years (Cosgrove et al ); however, this would require taxpayer dollars, with concomitant uncertainty in public and political commitment to such a long‐term effort.…”
Section: Diseases Associated With Privatization and Translocation Of mentioning
confidence: 99%